Improvement Of Social Studies Learning Results By Group Investigation Type (Gi) Of The Cooperative Learning Model On Elementary School In Padang - Yalvema Miaz (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
This research is motivated by Social Studies learning by Elementary School students in Padang. At that time, learning process is not so attractive by the students because it was centered on the teacher, and the students were merely act as listeners. Teachers more often lecturing students with a little question and answer session, and teachers rarely use certain learning model. The purpose of this study was to describe the learning outcome of the Social Studies students by using Group Investigation (GI) type of the Cooperative Learning Model in the Primary School. This model provides the opportunity for the students to search and find information from a variety of sources inside and outside the classroom. The type of this research is the Classroom Action Research (CAR) using qualitative and quantitative approaches. The subjects were teachers and 25 students of class V. The research procedures includes planning, implementation, observation, and reflection. The implementation consists of two cycles. If in the cycle I we have not gained the maximum result, then proceed to the cycle II. Each cycle consists of two stages of learning. The results showed an increase in student learning outcomes in the first cycle has increased in the second cycle with excellent qualifications. From the learning plans assesment result, in the first cycle was found 75%, and increased in the second cycle into 96.42%. From the observation in teacher aspect, an increase of 71.63% to 93.18% in the second cycle, while the aspect of students also increased from 71.50% to 93.18% in the second cycle. Student learning outcomes by using the GI type of the Cooperative Learning Model in Social Sdudies learning is also increased, namely the class average value of 72.21 in the first cycle increased to 88 in the second cycle.